Analysis of High Temperature Corrosion Attack on A36 Steel Galvanized Coating - Moch Arif Hidayatulloh; Prantasi Harmi Tjahjanti (Procedia of Engineering and Life Science, 2022)
One type of low carbon steel is A36 steel which is generally widely used in building and bridge construction. The weakness of the A36 is that it is susceptible to corrosion. The purpose of this thesis research is to provide a galvanic coating type ER-809 (Zinc Rich Cold) on the surface of A36 steel. The time of immersion or immersion in the galvanized solution varied for 30 seconds, 60 seconds and 1.5 minutes. Then the dry koroi test was carried out, which was heated to a temperature of 850 degrees Celsius with a holding time of 2 hours, 4 hours, and 6 hours. Furthermore, to find out the Corrosion Attack Rate (Corrotion Petration Rate / CPR) using the Weight Loss Method.